2015
DOI: 10.1097/iae.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Blood Flow Correlates to Aqueous Vascular Endothelial Growth Factor in Central Retinal Vein Occlusion

Abstract: Results: Fluorescein angiography found 20 ischemic and 25 non-ischemic type eyes. Aqueous VEGF concentration in the ischemic type was significantly higher than that in the non-ischemic type (P = 0.01). Arteriovenous passage time was significantly correlated to the logarithm of the aqueous VEGF concentration (P = 0.0001). MBR of the affected eye / MBR of the unaffected eye of the ischemic type was significantly lower than the non-ischemic type (P = 0.039). Additionally, MBR was significantly correlated both to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 26 publications
4
32
1
Order By: Relevance
“…A few research groups reported that the MBR-V in the ONH reflected the early phase of RT [27, 28], but these studies examined only central RVO cases. It thus remains unclear whether the mean blur rate in the optic nerve head as measured by LSFG reflects the circulation time obtained by FA in different ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A few research groups reported that the MBR-V in the ONH reflected the early phase of RT [27, 28], but these studies examined only central RVO cases. It thus remains unclear whether the mean blur rate in the optic nerve head as measured by LSFG reflects the circulation time obtained by FA in different ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Yamada et al. ), this is the first study to point to a role of FGF‐1 in impaired retinal blood flow in early DR. Overall, measurement of TRBF using Doppler OCT may be useful for predicting aqueous FGF‐1 levels and severity of hemodynamic disturbances in early DR.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, aqueous humour (AH) vascular endothelial growth factor (VEGF) was found to be associated with retinal blood flow in patients with central retinal vein occlusion (Yamada et al. ). More recently, the use of multiplex bead analysis allows for simultaneous analysis of multiple cytokines in small volumes and provides broader insight into the mechanisms involved in retinal hemodynamic alterations in early DR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Another study found that some cases of central RVO (CRVO) exhibited an increase in MBR in the ONH after IVB. 49 Most recently, MBR in the ONH in CRVO was reported to be correlated both with the aqueous concentration of VEGF and the arteriovenous passage time, 50 suggesting that LSFG may be useful for predicting the aqueous level of VEGF and the severity of CRVO. Thus, LSFG can be used to confirm the effectiveness of drug treatments targeting blood flow in different retinal ischemic diseases, leading to a better understanding of the pathogenesis of these retinal diseases.…”
Section: Monitoring Ocular Circulationmentioning
confidence: 99%